Acinetobacter strains carry two functional oligosaccharyltransferases, one devoted exclusively to type IV pilin, and the other one dedicated to O‐glycosylation of multiple proteins. Issue 5 (6th April 2015) - Harding, Christian M.; Nasr, Mohamed A.; Kinsella, Rachel L.; Scott, Nichollas E.; Foster, Leonard J.; Weber, Brent S.; Fiester, Steve E.; Actis, Luis A.; Tracy, Erin N.; Munson, Robert S.; Feldman, Mario F.
Summary Multiple species within the Acinetobacter genus are nosocomial opportunistic pathogens of increasing relevance worldwide. Among the virulence factors utilized by these bacteria are the type IV pili and a protein O‐glycosylation system. Glycosylation is mediated by O‐oligosaccharyltransferases (O‐OTases), enzymes that transfer the glycan from a lipid carrier to target proteins. O‐oligosaccharyltransferases are difficult to identify due to similarities with the WaaL ligases that catalyze the last step in lipopolysaccharide synthesis. A bioinformatics analysis revealed the presence of two genes encoding putative O‐OTases or WaaL ligases in most of the strains within the genus Acinetobacter. Employing A. nosocomialis M2 and A. baylyi ADP1 as model systems, we show that these genes encode two O‐OTases, one devoted uniquely to type IV pilin, and the other one responsible for glycosylation of multiple proteins. With the exception of ADP1, the pilin‐specific OTases in Acinetobacter resemble the TfpO/PilO O‐OTase from Pseudomonas aeruginosa. In ADP1 instead, the two O‐OTases are closely related to PglL, the general O‐OTase first discovered in Neisseria. However, one of them is exclusively dedicated to the glycosylation of the pilin‐like protein ComP. Our data reveal an intricate and remarkable evolutionary pathway for bacterial O‐OTases and provide novel tools for glycoengineering.